Endothelial glycocalyx: Clinical relevance and translational approach - Vélez, Jorge Luis (2019)
Endothelial glycocalyx is an undefined structure covering the luminal layer of the vascular endothelium and consisting mainly of three elements: proteoglycans, glycosaminoglycans and glycoproteins. It has different functions, such as the regulation of vascular permeability to liquids and molecules; transduction of the mechanical forces of vascular tension; regulation of coagulation and fibrinolysis cascades; and protection of leukocyte, platelet and pathogen adhesion. The determinants of a glycocalyx lesion can be of several types―e.g., increased tensile forces; reactive oxygen (O ) species; increased plasma level of substances such as sodium (hypernatremia), glucose (hyperglycemia) and cholesterol (hypercholesterolemia); and pro-inflammatory molecules. Any of the above-mentioned noxas, alone or combined, injure the glycocalyx. Its dysfunction will be clinically expressed as endothelial dysfunction, increased vascular permeability, filtration of lipoproteins to the subendothelium, activation of coagulation, or increased adhesion of leukocytes and platelets to the endothelium.